Transcriptome and metabolome analyses reveal molecular mechanisms of anthocyanin-related leaf color variation in poplar (Populus deltoides) cultivars - Peng, Xu Qian; Ai, Yu Jie; Pu, Yu Ting; Wang, Xiao Jing; Li, Yu Hang; Wang, Zhong; Zhuang, Wei Bing; Yu, Bing Jun; Zhu, Zhi Qi (Frontiers in Plant Science, 2023)
Colored-leaf plants are increasingly popular for their aesthetic, ecological, and social value, which are important materials for research on the regulation of plant pigments. However, anthocyanin components and the molecular mechanisms of anthocyanin biosynthesis in colored-leaf poplar remain unclear. In the present study, integrated metabolite and transcriptome profiling analysis was performed to explore the anthocyanin composition and the specific regulatory network of anthocyanin biosynthesis in the purple leaves of the cultivars ‘Quanhong’ (QHP) and ‘Zhongshanyuan’ (ZSY). A total of 39 anthocyanin compounds were detected by LC-MS/MS analysis. Twelve cyanidins, seven pelargonidins, five delphinidins, and five procyanidins were identified as the major anthocyanin compounds, which were differentially accumulated in purple leaves of QHP and ZSY. The major genes associated with anthocyanin biosynthesis, including structural genes and transcription factors, were differentially expressed in purple leaves of QHP and ZSY through RNA-sequencing (RNA-seq) data analysis, which was consistent with quantitative real-time PCR analysis results. Correlation analysis between RNA-seq data and metabolite profiles showed that the expression patterns of certain differentially expressed genes in the anthocyanin biosynthesis pathway were strongly correlated with the differential accumulation of anthocyanins. One R2R3-MYB subfamily member in the SG5 subgroup, Podel.04G021100, showed a similar expression pattern to some structural genes. This gene was strongly correlated with 16 anthocyanin compounds, indicating that Podel.04G021100 might be involved in the regulation of anthocyanin biosynthesis. These results contribute to a systematic and comprehensive understanding of anthocyanin accumulation and to the molecular mechanisms of anthocyanin biosynthesis in QHP and ZSY.